PENGARUH DIGITAL MARKETING DAN ONLINE CUSTOMER REVIEW TERHADAP NIAT BELI KONSUMEN PADA MARKETPLACE SHOPEE DI SURAKARTA - Pahlevi, Aga Reza; Lestari, Wuryaningsih Dwi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The research objective is to analyze the effect of digital marketing and oonline customer reviews on consumer purchase intentions at the Shopee marketplace in Surakarta. The samples in this study were people who had lived in Surakarta more than 4 years and used the Shopee application for more than one year and the samples taken were 100 pe ple. primary data type, data collection using a questionnaire. Data analysis used multiple linear regression tests, t tests, f tests using SPSS versi n 25. The results of the analysis show that digital marketing and oonline customer reviews each have a positive and significant effect on consumer purchase intentions at the Shopee marketplace in Surakarta